Gianni Vattimo and Nihilistic Christianity: Creating Open Concepts of Truth and Knowledge in the Age of Interpretation - Chambers, Stuart (Université d'Ottawa | University of Ottawa, 2009)
Borrowing largely from the Nietzschean and Heideggerian heritage, the works of Gianni Vattimo have been instrumental in promoting a nihilistic approach to Christianity. Vattimo’s method entails the weakening of metaphysics (absolute foundations) by exposing the violence so often associated with it. As a consequence, truth and knowledge are maintained as open concepts within the dialectical process. This does not mean that “strong relativism” now prevails as a legitimate philosophical viewpoint. What it does mean, however, is that Truth has simply been transformed into some intelligible form of truth. Moreover, Vattimo emphasizes that in the post-metaphysical (postabsolutist) world both secularism and nihilism are imperative to expanding truth and knowledge. As a result, it is argued that both philosophical positions are actually complementary to the roots of Christianity. Furthermore, I suggest that nihilism – in its positive form – not only expands the Christian message of charity, but also transforms it into its endless human potential.